Digestive enzyme activity and nutrient digestibility in meagre (Argyrosomus regius) fed increasing levels of black soldier fly meal (Hermetia illucens). (7th October 2020) - Guerreiro, Inês; Serra, Cláudia R.; Coutinho, Filipe; Couto, Ana; Castro, Carolina; Rangel, Fábio; Peres, Helena; Pousão‐Ferreira, Pedro; Matos, Elisabete; Gasco, Laura; Gai, Francesco; Oliva‐Teles, Aires; et al.
Abstract: The effect of partially replacing fishmeal (FM) by black soldier fly larvae meal ( Hermetia meal—HM) in meagre ( Argyrosomus regius ) diet was evaluated for nutrient digestibility and digestive enzyme activity. For that purpose, triplicate groups of fish (18.0 ± 0.02 g) were fed during 48 days either a control diet (CTR), without HM, or one of three diets including 100, 200 and 300 g/kg of HM, replacing 17, 35 and 52% of FM, respectively. Apparent digestibility coefficients (ADCs) of dry matter, energy, protein, lysine, isoleucine, leucine, phenylalanine, alanine, glutamate, glycine and serine presented a decreasing response with increased HM inclusion. Chitin ADC was null, independent of dietary HM inclusion. Total alkaline protease activity increased while trypsin activity decreased with dietary HM inclusion. No intestinal chitinolytic activity was detected. Intestinal alkaline protease zymogram revealed nine bands with proteolytic activity against casein, with molecular weights ranging between 15 and 75 kDa. Anti‐protease activity in the intestine was not affected by dietary inclusion of HM compared to the CTR diet. Overall, it is concluded that replacement of up to 17% FM with HM (100 g/kg HM inclusion level) in meagre diets has no major adverse effects in diet digestibility and digestive enzyme activity.